Two types of dysfunctional eighth component of complement (C8) molecules in C8 deficiency in man. Reconstitution of normal C8 from the mixture of two abnormal C8 molecules. - Tedesco, F (1983)
Restoration of hemolytic activity was examined in sera from seven unrelated eighth component of complement (C8)-deficient subjects. The sera fell into two groups, depending on whether hemolytic activity was restored by the addition of the beta-chain (group 1) or the alpha-gamma-subunit (group 2) purified from normal human C8. Antigenic analysis of these sera by double-immunodiffusion using anti-human C8 confirmed previous findings of a dysfunctional C8 in the four sera of group 1 and established the presence of a different dysfunctional C8 in one of the sera of group 2 when tested at a high concentration. Further characterization of the dysfunctional C8 molecules in the two sera by sodium dodecyl sulfate-polyacrylamide gel electrophoresis demonstrated that group 1 sera were missing the beta-subunit and group 2 sera were missing the alpha-gamma-subunit of the C8 molecule. Sera from either of these two groups alone did not produce hemolysis in hemolytic plates containing sheep erythrocytes coated with antibody and complement components up to C7 (EAC1-7) and C9. When sera from the two groups were added to adjacent wells in the hemolytic plates, a zone of hemolysis developed between the wells. The contribution of C8 alpha-gamma from the sera of group 1 and of C8 beta from those of group 2 to the lysis of EAC1-7 in the presence of C9 was confirmed by the inhibitory effect of specific antibodies against the two C8 subunits. In experiments in which hemolytic activity was reconstituted by mixing sera from group 1 with sera from group 2, the serum source of C8 beta (group 2) was the limiting reagent. The dysfunctional C8 molecule in this serum was able to bind to EAC1-7. Chromatographic analysis demonstrated that the generation of hemolytic activity in the mixture of the two sera resulted from the reconstitution of the C8 molecule rather than the sequential action of the two C8 subunits.